Unveiling Translation Patterns: A Study of English Novel Title in Indonesia - Ariansyah, Ahmad; Andriyanti, Erna; Ashadi, Ashadi (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
Effective titles captivate readers and encapsulate the essence of a work. This is especially true in novel translation, where titles bridge cultural gaps and introduce readers to new worlds. Thus, it is becoming a crucial consideration for translators when translating a title. They must transfer it meticulously from the source text (ST) into the target text (TT). One of the critical texts to be studied is a novel for its unique naming, which can be a significant challenge for translators. Hence, this study tried to examine how the novel title in English is translated into Indonesian and discover the following factors for using each title. Mixed method approached was to identify the type of title used towards the novel. It closes the gap that exists between qualitative and quantitative approaches. The data were collected from 114 English novels and their translations published before 2000. Accessibility was an essential criteria in selecting these titles, which are more consistent in terms of language and structure.This study discovered that the literal title translation type is the most prevalent, with 38.6% frequency, while the alternative title type denotes 35.1% frequency. Moreover, the researchers found 21.9% of data in the naturalized loan title category. The loan title with original orthography is the most minor category, with only 4.4% of the data. Further examination also highlights the need to consider shifts and meanings in exploring how Indonesian novel titles are translated. This paper also revealed several linguistic and cultural factors for utilizing each title type. As a result, title translation patterns offer translators practical insights to improve cross-cultural literary perspectives and the nuanced presentation of novel titles in varied language contexts.